Perceived current and potential role of libraries in citizen science initiatives: Stakeholders’ perceptions - Nurfarawahidah B.; Kiran K.; Yanti Idaya Aspura, M.K.; Mohd Faizal Hamzah (Malaysian Journal of Library and Information Science, 2025)
Citizen Science (CS) has become an important approach for involving the public in scientific research and facilitating collaboration between professional scientists and citizen volunteers. Libraries, which serve as accessible sources of information and centres for community engagement, are strategically positioned to support CS initiatives. The aim of this study is to explore how researchers, project managers and citizen scientists perceive the current and potential role of libraries in CS initiatives in the Malaysian context. Using a qualitative research design, semi-structured interviews were conducted with 13 individuals who are actively involved in CS projects in Malaysia. The thematic analysis, conducted using ATLAS.ti software, revealed different perceptions of current library services and identified opportunities for libraries to improve their role in CS. The results show that library services play a crucial role in providing access to resources and educational tools, supporting data management and analysis, and providing spaces for public engagement and outreach. In addition, libraries have the potential to become comprehensive resource centres for CS and serve as hubs for collaboration that promote public awareness and engagement. They can also act as centres for training and capacity building, equipping individuals with the necessary skills to contribute effectively to citizen science initiatives. Libraries can support the management and preservation of data and the contribution to achieving the Sustainable Development Goals (SDGs) through CS. These findings emphasise the transformative potential of libraries in promoting scientific literacy, sustainability and strengthening public engagement through CS.